Asparagus officinalis L. extract exhibits anti-proliferative and anti-invasive effects in endometrial cancer cells and a transgenic mouse model of endometrial cancer - Fang, Ziwei; Kong, Weimin; Zhao, Ziyi; Sun, Wenchuan; Xu, Guangxu; Clark, Leslie H.; Sullivan, Stephanie A.; Tran, Arthur-Quan; Zhou, Chang-Sheng; Sun, Delin; Zhao, Luyu; Wang, Jiandong; et al. (Frontiers in Pharmacology, 2024)
Endometrial cancer is the most common malignancy of the female reproductive system in the United States.Asparagus officinalis is a versatile, nutrient-dense, low-calorie vegetable that contains various bioactive metabolites that have shown a variety of biologic functions beneficial to health. The metabolites from asparagus officinalis extracts or asparagus officinalis extracts exhibit significant anti-tumorigenic activity in some preclinical models of cancer. This study was conducted to analyze the effects of Asparagus officinalis extracts on anti-tumorigenic activity in human endometrial cancer cell lines and a Lkb1 fl/fl p53 fl/fl transgenic mouse model of endometrial cancer. Treatment with increasing concentrations of Asparagus officinalis extracts significantly inhibited cell proliferation, reduced glycolytic activity, induced cellular stress and apoptosis, caused cell cycle G1 arrest, increased the sensitivity of cells to cisplatin, reduced cell adhesion and invasion, and activation of AMPK and inhibition of the AKT/mTOR and MAPK signaling pathways in endometrial cancer cells. Moreover, treatment with asparagus officinalis extract for 4 weeks resulted in a significant reduction in tumor growth in both obese and lean Lkb1 fl/fl p53 fl/fl mice. Overall, these findings provide strong pre-clinical evidence for the potential therapeutic benefit of Asparagus officinalis extract as a novel dietary strategy for the treatment of endometrial cancer.